Cartel Practices in Relation to Rice Supply Chains - Hendy Febrianto Kurniawan; Eva Achjani Zulfa; Audaraziq Ismail; Ahmad Sarinawi; Bayquni Bayquni (Pelopor Publikasi Akademika, 2023)
This study discusses cartel practices in the rice supply chain with a focus on the implications of the Indonesian Farmer Shop (TTI) program. The complex rice supply chain has affected the price of consumer rice and farmers' grain. This study uses a qualitative approach with a normative juridical method and organized crime theory. The results of the study show that although the TTI program has a clear basis, cartel practices emerge due to the domination of actors in rice marketing and laxity in implementing policies. The TTI program creates shorter supply chains, but cartel practices still exist. This research reveals that cartel practices arise from the implementation of the TTI program which is controlled by certain parties with strong control. Obstacles in bookkeeping and supply management also influenced the emergence of cartels. Cartel practices arise not because of regulations, but because of their implementation which tends to be abused by cartel actors.